Early superior cavopulmonary connection with preoperative computer tomography shows comparable outcomes for infants following Norwood palliation. (28th May 2022) - Bellsham-Revell, Hannah R; Tarmahomed, Abdulla; Chou, Catie; Wong, James; Mathur, Sujeev; Vigneswaran, Trisha; Salih, Caner
Abstract: OBJECTIVES: There is increasing evidence that performing superior cavopulmonary connection (SCPC) at 3 months reduces mortality: reducing the risky 'interstage' period, volume off-loading the ventricle and reducing coronary steal, hopefully preserving ventricular function. Our objective was to describe our experience of early SCPC with preoperative computer tomography (CT) assessment compared to later connection at 6 months. METHODS: Patients undergoing Norwood procedure from 2005 to 2020 were divided into 2 eras were described and compared. Era 1 from 2005 to 2016 when SCPC was undertaken at 6 months: and era 2 (2017–2020) when an earlier operation was performed. Demographics, mortality (interstage, early and late following SCPC) and data on postoperative course and complications were recorded. RESULTS: In era 1, 191 patients underwent Norwood (120 survivors to SCPC) and 28 patients (23 survivors) in era 2. There were no significant differences in the demographics. Interstage mortality was 17.8% in era 1 and 8.0% in era 2 but not significantly significant ( P  = 0.22). The median (interquartile range) age at pre-imaging and SCPC was significantly lower: 99 (81–120) vs 77 (47–102) days and 175 (117–208) vs 106 (102–122) days in era 1 vs era 2 ( P  < 0.005). Weight was lower at SCPC in era 2 [mean (standard deviation) 6.2 kg (1.2) vs 5.1 kg (0.8), P  < 0.05]. Intubation time and total length of stay were not statistically different. Median intensive care unit stay was statistically significantly longer, but not clinically significant: 2.5 (2–4) vs 3 (3–5) days, respectively ( P  < 0.05). There was no significant difference in early or late mortality, rates of diagnostic or interventional catheter, postoperative magnetic resonance imaging/CT or stroke. Logistic regression analysis demonstrates increasing age at SCPC was associated with increased chance of stroke or early death ( P  = 0.043). CONCLUSIONS: Early SCPC with CT assessment is feasible and although intensive care unit length of stay was slightly longer there was no change in the overall length of stay and no change in postoperative mortality or complications. Abstract : Congenital heart disease with left heart structures, which were unable to support the systemic circulation, was universally fatal until the Norwood procedure [1] was developed in the 1980s and this procedure is now routine in many cardiac centres.